Language teaching and learning : new dimensions and interventions - Pandian, Ambigapathy; Ching Ling, Christine Liew; Ai Lin, Debbita Tan; Muniandy, Jayagowri; Choo, Lee Bee; Hiang, Toh Chwee (Cambridge Scholars Publishing, 2014)
In every discussion on the role that language plays in our lives, every orator - from prominent politicians and corporate figures to linguists, educational experts, and others - concedes that language is important in all spheres of life. Language is both personal and introspective, as well as public and communal. Without it, we would not be able to communicate and articulate our thoughts and feelings to ourselves, to those in our inner circles, and to those in the world at large. Without it, we would not be able to establish partnerships and collaborations, and to unite peoples of diverse back.